Followership among jordanian nurses: A cross-sectional online study - Wafaa T. ALQadrie; Ali M. Saleh; Sami AL-Rawashdeh; Ola N. Alfuqaha; Suheir I. Abdallah (PLoS ONE, 2025)
Background In recent years, the concept of followership has gained significant attention, challenging the traditional leadership-centric view of organizational management positions. While effective followership is vital to the success of any organization, it has often been overlooked, especially in healthcare, where teamwork is crucial. Aim The current study aimed to identify the followership styles of nurses in Jordan and examine how these styles relate to nurses’ demographic and work-related characteristics. Method A descriptive cross-sectional design was employed. Using a multistage sampling approach, 351 registered nurses were recruited from governmental, private, and teaching hospitals across northern, central, and southern Jordan. Data were collected through an online survey using the validated Kelley Followership Questionnaire–Revised (KFQ-R). Both descriptive and inferential statistical analyses were conducted. Results Findings revealed that the predominant followership style was exemplary (68.7%), followed by the pragmatist (31.3%). Chi square test revealed statistically significant difference between followership style and marital status (χ² (1) = 6.193, p = .013), working area (χ² (2) = 7.405, p = .025), nursing care delivery system (χ² (3) = 13.926, p = .003), and Decision-making style (χ² (3) = 17.173, p = .001). The binary logistic regression was significant, χ² (26) = 67.77, p < .001, identifying participatory decision-making style, working area, and nursing care delivery system as significant predictors of exemplary followership. Conclusion The study found that nurses working in participatory decision-making environments, team-based models of care, and high-intensity units such as emergency departments were more likely to exhibit the characteristics of exemplary followers. Nurse leaders and managers should foster work environments that promote autonomy, support shared decision-making, and encourage active team engagement. These findings emphasize the critical role of effective followership in advancing collaborative practice, optimizing clinical decision-making, and strengthening workforce performance, underscoring its integration into nursing education, leadership development program, and organizational policy.